The use of RAPD markers to Detect the genetic diversity of E. coli isolates from Kirkuk city environment - Waa'd M. Raoof; Akeel H. Al-Assi; Shaimaa Monshed Morshed (Tikrit Journal of Pure Science)
The environmental samples we were collected about 130 samples from the soil and water and were dividing to (71) , (59) water and soil samples resectively.